Pseudomonas viridiflava pathogenicity in Agave inaequidens and inhibition with essential oils - Hernández-Valencia, Adelaida Stephany; Ochoa-Martínez, Daniel Leobardo; Hernández-Pérez, Anselmo; Martínez-Palacios, Alejandro; Tapia-Vargas, Luis Mario (Revista Mexicana de Ciencias Agrícolas, 2024)
The bacterium Pseudomonas viridiflava (Burkholder, 1930) causes economic damage in beans (Phaseolus vulgaris L.); it has been shown that it can affect more than 50 hosts (Saygili et al., 2008), among which are alfalfa (Medicago sativa), apple tree [Malus pumila var. domestica (Borkh.) CK Schneid.] (Alimi et al., 2011), and broccoli (Brassica oleracea L.); however, in Origanum vulgare, there is no report of any damage on agave mezcalero (Agave inaequidens K.Koch), a species still little studied; this research was based on the evaluation of the effects of the bacterium Pseudomonas viridiflava in the process of imbibition in seeds of Agave inaequidens; on the other hand, the tolerance of the bacterium to the essential oils of cinnamon (Cinnamomum verum Blume), clove (Syzygium aromaticum L.), and oregano (Origanum heracleoticum Rchb.) was evaluated, as preliminary studies for the ecological, organic, agrochemical-free management strategy in crops affected by Pseudomonas viridiflava; it was found that the concentration of 25% of oregano and cloves oil was efficient in the development of the bacterium under in vitro conditions; in contrast, in the germination process based on the imbibition of the seed, there was no reduction in the percentage of germination or signs of damage due to the effect of the bacteria.
Keywords: Agave inaequidens; Agave mezcalero; Pseudomona viridiflava; biological control